Community Health Workers in Nepal: A Systematic Review of Their Role in Health System Strengthening - Ghimire, Shubhechchha; Bhatt, Prakash Raj (Asian Journal of Population Sciences, 2025)
Community Health Workers are vital in strengthening Nepal's healthcare system, particularly in underserved rural and remote regions, significantly reducing mortality rates and achieving national health goals. The paper aims to systematically evaluate the literature on CHWs' role in health system strengthening in Nepal, examining their characteristics, impact, motivations, and challenges. A mixed-method systematic review was conducted using PubMed, Research4life, and Google Scholar databases. Eight studies (5 qualitative, 1 quantitative, and 2 mixed methods) were analyzed using the Mixed Method Appraisal Tool 2018 and thematic analysis. Five major themes emerged: (1) Socio-demographic characteristics - CHWs are predominantly female volunteers with varying educational backgrounds; (2) Evolving roles - expanding beyond traditional maternal and child health to include non-communicable diseases; (3) Motivation factors - driven by community service and professional development opportunities; (4) System integration - serving as crucial intermediaries between communities and healthcare facilities; and (5) Implementation challenges - including limited resources, insufficient training, and inadequate incentives. While CHWs are essential to Nepal's healthcare system, particularly in delivering culturally competent primary health services, there is a critical need for sustainable support mechanisms. Enhanced capacity-building initiatives, improved supervision systems, and appropriate incentives are necessary to retain experienced CHWs and maximize their impact. Investment in CHW programmes is crucial for strengthening Nepal's health system and achieving better community health outcomes, especially in rural areas.